2014
DOI: 10.7317/pk.2014.38.5.656
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Release Behavior of Atorvastatin Calcuim - Encapsulated Polyoxalate Microspheres

Abstract: Atorvastatin calcium-loaded polyoxalate (POX) microspheres were prepared by an emulsion solvent-evaporation/extraction method of oil-in-oil-in-water (O 1 /O 2 /W) for sustained release. We investigated the release behavior according to initial drug ratio, molecular weight (M w ) and concentration of POX and concentration of emulsifier. The microsphere was characterized on the surface, the cross-section morphology and the behavior of atorvastatin calcium release for 10 days by scanning electron microscopy (SEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The treatment of H 2 O 2 caused morphological changes of the particles with size increase of ∼1135.2 nm (Figure D) and generation of many holes (Figure C). The holes of the particles were generated by H 2 O 2 -induced degradation of oxalyl ester bond, which can be decomposed to CO 2 and incorporated compounds, leading to release drug rapidly . In addition, the size of the particles showed upper 10000 nm, which was generated by aggregation of destroyed particles (Figure D).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The treatment of H 2 O 2 caused morphological changes of the particles with size increase of ∼1135.2 nm (Figure D) and generation of many holes (Figure C). The holes of the particles were generated by H 2 O 2 -induced degradation of oxalyl ester bond, which can be decomposed to CO 2 and incorporated compounds, leading to release drug rapidly . In addition, the size of the particles showed upper 10000 nm, which was generated by aggregation of destroyed particles (Figure D).…”
Section: Resultsmentioning
confidence: 74%
“…The holes of the particles were generated by H 2 O 2induced degradation of oxalyl ester bond, which can be decomposed to CO 2 and incorporated compounds, leading to release drug rapidly. 18 In addition, the size of the particles showed upper 10000 nm, which was generated by aggregation of destroyed particles (Figure 2D). These results suggest that H 2 O 2 -sensitive degradation of TPOX nanoparticles contributes to release rapidly incorporated tyrosol and entrapped drugs through breakdown of polyoxalates depending on the H 2 O 2 concentration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main drawbacks of conventional co-precipitation method are broad size distribution and agglomeration of iron oxide nanoparticles due to their high surface energy. To avoid the imitation of co-precipitation during washing process, surface of iron oxide nanoparticles was modified with formation of a polymeric layer such as dextran, chitosan, polyvinyl alcohol (PVA), polyethylene glycol (PEG), or polyvinylpyrrolidone (PVP) [10][11][12][13][14]. For example, Sousa et al found that citric acid coating improved the stability and biocompatibility of magnetite (Fe3O4) nanoparticles synthesized via co-precipitation with saturation magnetization of 26 emu/g.…”
Section: Introductionmentioning
confidence: 99%